Enshrine the Principle of the Common Heritage of Humanity Within the Framework of International Law - Issa, Miami; Jafaar, Mahmood (Journal of Legal Sciences, 2023)
The international community began to realize, following the discovery of  vast wealth in areas that fall outside the territorial limits of states sovereignty, that the huge difference in scientific and technological development between developed and developing countries may give developed countries the opportunity to exploit these wealth, and this, in turn, will lead to a widening gap between countries, developed and developing countries, and the consolidation of the principle of inequality due to the lack of third world countries with the capabilities that allow them to participate in the exploitation of these wealth, and when these concerns came to the fore in the United Nations General Assembly in 1967, Ambassador Arvid Bardo, the permanent representative of the State of Malta to the United Nations, called for August 17, 1967 to include in the agenda (D-22) of the General Assembly of the United Nations a proposal to study the issue of allocating the seabed and ocean floor and subsoil beyond the territorial limits of states for peaceful purposes only and the use of its resources for the human interest, as this proposal was approved by the General Assembly of the United Nations Several legal steps have been taken to put it into practice.